Neonatal LPS Administered Before Sensitization Reduced the Number of Inflammatory Monocytes and Abrogated the Development of OVA-Induced Th2 Allergic Airway Inflammation - Gao, Liuchuang; Wu, Min; Liu, Hangyu; He, Miao; Jiang, Han; Shang, Runshi; Wang, Qiangqiang; Song, Zhu; Huang, Yafei; Han, Junyan (Frontiers in Immunology, 2021)
It is becoming increasingly clear that environment factors during early life play a pivotal role in the development of allergic asthma. Among these, a traditional farm is one of the strongest protective environments and the protective effects have been attributed to the high-level exposure to LPS on farms. However, the underlying mechanisms remain elusive, especially in OVA-induced neonatal allergic asthma model. Here, we used OVA-induced asthma model in two age groups, neonatal and adult, when mice were first sensitized with peritoneal OVA/alum as neonates and adults, respectively. LPS was injected in the peritoneal cavity before OVA/alum sensitization. The effects of LPS treatment on the allergic airway inflammation in the lung and the immune milieu in the peritoneal cavity were determined and compared between these two age groups. We found that LPS treatment abrogated the development of Th2 allergic airway responses in neonatal group. In adult group, the ameliorated Th2 allergic responses were accompanied with Th17 responses and neutrophil infiltration upon LPS treatment. We further investigated the immune milieu in the peritoneal cavity to elucidate the underlying mechanisms of this age-dependent difference. Our data show that in neonatal mice, LPS treatment significantly reduced the number of inflammatory monocytes in the peritoneal cavity. In adult group, LPS treatment shifted the function of these cells which associated with Th1 and Th17 polarization. Our results provide more evidence that immunity in early life is distinct from that in adults, especially in the peritoneal cavity and emphasize the importance of the timing for the intervention of allergic asthma. Our results suggest that LPS treatment during early life is protective for the development of Th2 allergic responses. On the other hand, it might lead to more severe phenotype of asthma when dampening the Th2 responses in adult mice.